An estimation of productivity in the Montalban Wa-wa River with a listing of some green algae found in the river - Chua, Emil Bermin (Animo Repository, 1998)
The study was conducted at the Montalban Wa-wa river to determine the estimate productivity of the river. The different physico-chemical characteristics that were measured were temperature, pH, transparency, dissolved oxygen, alkalinity, and nutrient (Silicat, Phosphate and Nitrate) content. Site 2 has a greater biomass estimate than in Site 1. A total of seven genera of green algae were identified in this study.